Desenvolvimento de um protótipo de sistema informatizado de controle para gestão da saúde - Marchesan Neto, Ricardo (2018)
The perception of how much software is constantly evolving is common. In the field of health information records are necessary, both for the care processes and for the bureaucratic processes, the information system allows the quality and productivity of health care. The objective of developing a prototype that makes possible the creation of a computerized and interconnected system for public health management. A software prototype was implemented using Scrum, Bootstrap, XAMPP, PHP, Laravel, Database Management System (DBMS), MySQL, PhpStorm, Firefox. As result a prototype of an agile and interconnected system was elaborated. I emphasize the need for a repagination in the current system to reduce costs and speed up service.